The Influence of Using Teams-Games-Tournament (TGT) on Simple Present Tense - Ahmad Munawir; Irmayanti Irmayanti; Muhammad Ridwan (EDUVELOP, 2018)
The objective in this research is to find out the influence of using Teams – Games – tournament (TGT) towards Simple Present tense at seventh grade of Smp Negeri 5 Wonomulyo. This is a quantitative pre-experiment research design where the researcher chose one group pre-test post-test research design. The population of this research is the students of seventh grade of SMP Negeri 5 Wonomulyo where the total number of population were 155 of five classes. The sample of population was 28 students where The researcher used technique simple purposive sampling. The result of this research proves that there is an influence of using TGT on simple present tense mastery. According to calculation, it can be seen that mean score of pre-test was 56,78 and mean score of post-test was 72,5. moreover, based on the result of analysis the data, the value of t-table is 11,22 and the value of t-test is 1.703, it means that 11,22 > 1.703. It can be concluded that learning Simple present tense by using TGT technique has an influence towards the students simple present tense mastery of the seventh grade of SMP Negeri 5 Wonomulyo.